Current collector for ultrasonic-assisted directional energy deposition and preparation method and system thereof
By combining magnetron sputtering and electrodeposition in the acid sulfate system and using ultrasonic impact treatment, the problem of uneven deposition of composite liquid collector copper foil is solved, the grain structure is refined, and the cycle life and conductivity of lithium batteries are improved. , reducing corrosion.
Patent Information
- Application Number
- CN202411261426.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The water-electroplating deposition layer of traditional composite liquid-collection copper foil has problems of uneven deposition, looseness and randomness, resulting in large interface resistance and easy falloff, affecting the performance of lithium batteries.
Using ultrasonic assisted directional energy deposition method, magnetron sputtering and electrodeposition are combined in the acid sulfate system, and the Cu layer is treated with ultrasonic impact. The deposition process is transformed into electrochemical control, refines the grain structure, and enhances the composite copper foil and Contact angle of the electrolyte and adhesion of the active material.
The electrodeposition effect of the Cu layer is improved, the corrosion of the electrolyte on the composite liquid collecting copper foil is reduced, the electrolyte resistance of the film layer and the conductivity of the electrode are improved, and the cycle life of the lithium battery is extended.
Smart Images

Figure BDA0005035797390000081 
Figure BDA0005035797390000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of current collectors, and in particular relates to a current collector for ultrasound-assisted directional energy deposition and a preparation method and system thereof. Background Art
[0002] The negative electrode current collector of traditional lithium-ion batteries is copper foil. With the development of lithium battery technology, the high energy density, light weight and flexibility of lithium-ion batteries have become people's pursuit. Thinning copper foil can achieve the lightweight of lithium-ion batteries, improve energy density and reduce costs. However, due to the limitations of preparation technology, it is difficult to reduce the thickness of copper foil. In addition, after the copper foil is thinned, the mechanical strength is reduced, resulting in reduced processing performance, so new thinning technology is needed.
[0003] The composite current collector copper foil is made by plating a certain thickness of copper on both sides of the polymer material layer, with the upper and lower copper layers being about 1μm thick each, forming a "sandwich" composite structure. The more mature preparation process is to first use magnetron sputtering to deposit a NiCr film on the polymer film substrate as a primer, then deposit a 25-50nm thick Cu film to metallize the substrate surface, and then deposit a 1μm copper layer on both sides of the metallized surface of the composite copper foil by water electroplating to make a composite copper foil.
[0004] As a key technology for the production and application of composite current collector copper foil, water electroplating deposition technology has the advantages of low process cost and good process flexibility. However, it also has problems such as uneven thickness of the deposited layer, loose porosity, and difficult to control the crystal morphology. This can easily lead to problems such as large interface resistance between the active material and the composite current collector copper foil, easy falling off, etc., which in turn will lead to a decline in battery performance.
[0005] Therefore, how to overcome the problem of uneven, loose and irregular deposition of the water electroplating surface deposited layer of the current collector is a technical problem that urgently needs to be solved in this field.
[0006] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention
[0007] The embodiments of the present disclosure at least provide a current collector for ultrasound-assisted directional energy deposition and a preparation method and system thereof.
[0008] In a first aspect, an embodiment of the present disclosure provides a method for preparing a current collector for ultrasound-assisted directional energy deposition, comprising the following steps: step S1, sputtering Cu on the surface of a substrate layer by magnetron sputtering to obtain a carrier foil; step S2, thickening the carrier foil by electrodeposition of copper on the carrier foil in an acidic sulfate system to obtain a Cu layer, and simultaneously performing ultrasonic impact treatment on the carrier foil, wherein the frequency of the ultrasonic wave is 10-30 MHz and the power does not exceed 100 W.
[0009] In an optional embodiment, sputtering Cu on the surface of the substrate layer by magnetron sputtering in step S1 specifically includes the following steps: step S11, adjusting the vacuum degree of the chamber of the magnetron sputtering plating machine, and starting the cathode and the drive roller; step S12, introducing argon gas into the chamber and increasing the power of the ion source to ionize the argon gas, thereby cleaning the surface of the substrate; step S13, introducing sputtering gas argon gas, and using a copper target to form a Cu layer on the surface of the substrate layer by magnetron sputtering, that is, obtaining a carrier foil; step S14, repeating steps S11-S13 on the other side of the substrate layer.
[0010] In an optional implementation, the power adjustment range of the ion source in step S12 is 800-1000W.
[0011] In an optional embodiment, in step S13, the purity of the sputtering gas argon is not less than 99.99%, the flow rate is 400-600 sccm, the pressure in the chamber is in the range of 0.3-0.5 Pa, and the power of magnetron sputtering is 5-50 Kw.
[0012] In an optional implementation, the thickness of the Cu layer after thickening in step S2 is 500 nm-5 μm.
[0013] In an optional implementation, the power of the ultrasonic impact treatment in step S2 is 20-60W.
[0014] In a second aspect, an embodiment of the present disclosure further provides a current collector for ultrasound-assisted directed energy deposition prepared by the method described above, comprising: a substrate layer; a Cu layer, wherein the Cu layer is arranged on both sides of the substrate layer.
[0015] In an optional embodiment, the substrate layer includes any one of a biaxially oriented polypropylene film, a cast polypropylene film, a polyethylene terephthalate film, a polyimide film and a polyethylene naphthalate film; and the thickness of the substrate layer is 3-20 μm.
[0016] In an optional implementation, the material of the Cu layer is copper or copper alloy; the thickness of the Cu layer is 500 nm-5 μm.
[0017] In a third aspect, an embodiment of the present disclosure further provides an ultrasound-assisted directed energy deposition system, which adopts the method as described above to prepare a current collector, and is characterized in that it includes: an electroplating pool, in which an acidic sulfate system is arranged; and at least one ultrasonic generator is arranged above the electroplating pool.
[0018] The beneficial effects of the present invention are as follows: the current collector for ultrasound-assisted directed energy deposition and the preparation method and system thereof apply an ultrasonic field in an acidic sulfate system, so that the Cu deposition process is transformed from diffusion control to electrochemical control, which accelerates the mass transfer process and improves the Cu electrodeposition effect; at the same time, ultrasound has a grain refinement effect, and in the process of utilizing ultrasonic impact to assist deposition, the microcrystalline structure on the surface of the composite copper foil can be increased, thereby increasing the contact angle between the composite current collector copper foil and the electrolyte, reducing the wettability between the two, thereby reducing the corrosion of the electrolyte to the composite current collector copper foil, and improving the electrolyte resistance of the film layer; in addition, the refined grains make the surface of the composite current collector copper foil rough, which helps to improve its adhesion to the active material, thereby improving the conductivity and structural stability of the electrode, and the above effects can ultimately further improve the cycle life of the lithium battery.
[0019] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description and claims.
[0020] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below for detailed description as follows. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.
[0023] In this document, as used herein, expressions such as "at least one of..." when following a list of elements modify the entire list of elements rather than modifying the individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0024] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.
[0025] In the production process of traditional electrolytic copper foil or composite current collector copper foil, chromium plating technology is usually used to enhance its corrosion resistance. However, chromium, as a heavy metal element, poses a potential pollution risk to the environment. International Publication No. WO2024 / 011536A1 provides a method for preparing a copper composite current collector. The method adjusts the temperature of the copper plating roller to have different temperature zones, so that the copper metal layer can be plated on the surface of the polymer film at different speeds, and the growth rate of copper crystals in the copper metal layer is different, thereby achieving an increase in the roughness of the copper composite current collector, thereby increasing the contact area between the active material in the battery and the copper composite current collector, and extending the cycle life of the battery. However, this method is difficult to produce and has high production costs, which is not conducive to promotion.
[0026] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present disclosure during the disclosure process.
[0027] As an elastic mechanical wave in a physical medium, ultrasound has a unique "mechanical disturbance effect" and "cavitation effect" that affect the liquid phase mass transfer process, and mainly exists in the form of electrochemical control. Ultrasonic waves can effectively solve problems such as slow liquid phase mass transfer and insufficient ion supply near the electrode during electrodeposition under static conditions.
[0028] The disclosed embodiment provides a method for preparing a current collector for ultrasound-assisted directional energy deposition, comprising the following steps: step S1, sputtering Cu on the surface of a substrate layer by magnetron sputtering to obtain a carrier foil; step S2, thickening the carrier foil by electrodeposition of copper on the carrier foil in an acidic sulfate system to obtain a Cu layer, and simultaneously subjecting the carrier foil to ultrasonic impact treatment, wherein the frequency of the ultrasonic wave is 10-30 MHz and the power does not exceed 100 W.
[0029] In some embodiments, specifically, the sputtering method may be alternating current (AC) magnetron sputtering, direct current (DC) magnetron sputtering, or radio frequency (RF) magnetron sputtering. Since the copper layer is a conductor, direct current (DC) magnetron sputtering is preferred.
[0030] In some embodiments, specifically, sputtering Cu on the surface of the substrate layer by magnetron sputtering in step S1 specifically includes the following steps: step S11, adjusting the vacuum degree of the chamber of the magnetron sputtering plating machine, and starting the cathode and the drive roller; step S12, introducing argon gas into the chamber and increasing the power of the ion source to ionize the argon gas, and then cleaning the surface of the substrate; step S13, introducing sputtering gas argon gas, and using a copper target to form a Cu layer on the surface of the substrate layer by magnetron sputtering, that is, obtaining a carrier foil; step S14, repeating steps S11-S13 on the other side of the substrate layer.
[0031] In some embodiments, specifically, the power adjustment range of the ion source in step S12 is 800-1000W.
[0032] In some embodiments, specifically, in step S13, the purity of the sputtering gas argon is not less than 99.99%, the amount of the sputtering gas is 400-600 sccm, the pressure in the chamber is in the range of 0.3-0.5 Pa, and the power of the magnetron sputtering is 5-50 Kw.
[0033] In some embodiments, specifically, the thickness of the Cu layer after thickening in step S2 is 500 nm-5 μm, preferably 800 nm-1.5 μm.
[0034] In some embodiments, specifically, the power of the ultrasonic impact treatment in step S2 is 20-60W.
[0035] The disclosed embodiment also provides a current collector for ultrasound-assisted directed energy deposition prepared by the method described above, comprising: a substrate layer; a Cu layer, wherein the Cu layer is arranged on both sides of the substrate layer.
[0036] In some embodiments, specifically, the substrate layer includes any one of biaxially oriented polypropylene film (OPP), cast polypropylene film (CPP), polyethylene terephthalate film (PET), polyimide film (PI) and polyethylene naphthalate film (PEN); the thickness of the substrate layer is 3-20 μm.
[0037] In some embodiments, specifically, the material of the Cu layer is copper or copper alloy; the thickness of the Cu layer is 500 nm-5 μm, preferably 800 nm-1.5 μm.
[0038] The disclosed embodiment also provides an ultrasound-assisted directed energy deposition system, which uses the method described above to prepare a current collector, and is characterized in that it includes: an electroplating cell, wherein an acidic sulfate system is arranged in the electroplating cell; and at least one ultrasonic generator is arranged above the electroplating cell.
[0039] Some embodiments of the present invention are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0040] A method for preparing a current collector for ultrasound-assisted directional energy deposition comprises the following steps:
[0041] Step S1, sputtering Cu on the surface of the substrate layer by magnetron sputtering to obtain a carrier foil:
[0042] Step S11, in the chamber of the winding magnetron sputtering plating machine, place the processed flexible substrate on the unwinding roller of the unwinding chamber and wind it onto the winding roller; at the same time, place the required copper target materials on the corresponding cathode target positions of the chamber in sequence, and adjust the distance from the target material to the substrate surface to 10 cm; close all chamber doors, turn on the fore pump and the molecular pump in sequence, and wait until the vacuum degree of the chamber reaches 5×10 -4 When the pressure drops to 0.05 Pa, fill in process gas until the process vacuum is reached, open the cathode and drive roller to start coating, and control the winding speed at 5-12 m / min.
[0043] Step S12, argon gas is introduced into the vacuum chamber, and the argon gas is ionized by providing 800 W of power to the ion source, thereby cleaning the surface of the substrate;
[0044] Step S13, introducing sputtering gas argon with a purity of not less than 99.99% into the chamber, the argon amount is 400 sccm, the chamber pressure is stabilized at 0.3 Pa, and a copper layer of a certain thickness is formed on the base film using a copper target by dual rotating cathode and DC magnetron sputtering to obtain a copper carrier foil, and the dual rotating cathode and DC magnetron sputtering power is 5Kw to 50Kw.
[0045] Step S14: the copper carrier foil on the other side of the substrate layer is prepared by the same process as above.
[0046] Step S2, in an acid sulfate system, copper is electrodeposited on the carrier foil to obtain a Cu layer by electrodeposition, the speed is controlled at 2-15 m / min, and the carrier foil is subjected to ultrasonic impact treatment at the same time, the frequency of the ultrasonic wave is 10-30 MHz, and the power is 0-100 W.
[0047] Specifically, after the copper carrier foil is obtained by magnetron sputtering, it also includes electroplating copper, inputting the carrier foil with the metal copper sputtering layer into the copper electroplating tank, and controlling the line speed at 2-15m / min. Any conventional acid electrolytic copper plating solution in the art can be used for copper plating, and the electroplating current density is 0.1-2A / d. The electroplated copper is acid electrolytic copper plating, and the thickness of the copper layer obtained by electroplating copper is 500nm~5um, preferably 800nm~1.5um. Ultrasonic impact treatment will also be carried out during the thickening process of electroplated copper. The ultrasonic impact treatment step specifically includes: according to the width of the copper plating tank, 1-5 ultrasonic generators can be evenly arranged perpendicular to the direction of product travel to form an ultrasonic impact system. The ultrasonic vibration system is placed above the tank liquid, and the surface of the copper foil is microcrystalline treated with 10-30Hz ultrasound, and the ultrasonic field power is set at 0-100w, preferably 20-60w. By adjusting the frequency and power of the ultrasonic vibration, copper foil with different grain refinement surfaces can be obtained.
[0048] In some embodiments, specifically, two or more ultrasonic impact systems may be sequentially arranged above the copper plating tank in the transport direction of the composite current collector to further enhance the grain refinement effect of the composite current collector.
[0049] Specifically, the winding speed in step S11 is set to 10 m / min, the double rotating cathode and DC magnetron sputtering power in step S13 are set to 10 Kw, the ultrasonic frequency is 30 MHz, and two ultrasonic generators are set in parallel above the electroplating cell. The ultrasonic power and some performance data are shown in Table 1 below:
[0050] Table 1
[0051]
[0052]
[0053] Corrosion resistance test: The corrosion resistance of the original metallized plastic current collector copper foil and the metallized plastic current collector copper foil was evaluated after being immersed in an electrolyte containing 1000 ppm water for 240 h, and their surface morphology was observed.
[0054] Specifically, compared with Examples 1-8, after adding ultrasonic field 2 in Examples 7-8, the peel strength of the current collector and the battery cycle life are improved.
[0055] Specifically, comparing Examples 1-8 and Comparative Examples 1-3, the original metallized plastic current collector copper foil showed corrosion and discoloration after being immersed in the electrolyte. The surface of the metallized plastic current collector copper foil deposited with appropriate power and frequency ultrasonic assisted deposition was intact and showed no corrosion and discoloration, which indicates that the metallized plastic current collector copper foil deposited with ultrasonic assisted deposition is more stable than the original copper foil in the electrolyte. This is because the ultrasonic field has a significant grain refinement effect, which can increase the microcrystalline structure and number on the surface of the composite copper foil, thereby increasing the contact angle between the composite current collector copper foil and the electrolyte, reducing the wettability between the two, thereby reducing the corrosion of the electrolyte to the composite current collector copper foil, and improving the electrolyte resistance of the film layer. At the same time, it can be seen that the higher the power of the ultrasonic field, the more obvious the refinement effect, but it should also be noted that when the power is greater than 100W, such as Comparative Example 2, although the refinement effect is improved, it will also cause a decrease in peel strength.
[0056] Peel strength test: used to evaluate the bonding strength between copper foil and active material. 80% artificial graphite powder, 10% conductive carbon black and 10% polyvinylidene fluoride were mixed in proportion, and then an appropriate amount of N-methylpyrrolidone (NMP) was added under stirring to obtain a uniform slurry. Use a scraper to evenly apply the slurry on the surface of the original metallized plastic current collector copper foil and the metallized plastic current collector copper foil after ultrasonic assisted deposition. Then, the coated electrode sheet was dried in a vacuum oven at 60°C for 12 hours to test its adhesion.
[0057] Specifically, comparing Examples 1-8 and Comparative Examples 1-3, the bonding strength between the graphite particles and the original metallized plastic current collector copper foil is 0.35 N / cm, while the bonding strength of the metallized plastic current collector copper foil after ultrasonic assisted deposition is greater than this data. Obviously, the bonding strength between the metallized plastic current collector copper foil and the active material after ultrasonic assisted deposition is significantly increased. This is because the grain refinement helps the surface of the composite copper foil to become rougher, thereby enhancing the bonding strength between the electrode and the current collector, and further improving the conductivity and structural stability of the electrode. At the same time, it can be seen that setting multiple ultrasonic fields during the thickening process of electrodeposited copper is more conducive to improving the peeling strength.
[0058] Battery cycle life test: According to the standard GB / T31484-2015 "Requirements and test methods for cycle life of power batteries for electric vehicles", the performance of metallized plastic current collector copper foil deposited by ultrasonic assisted deposition is tested. The specific test conditions include: at 25°C, 1C charge and discharge rate, 100% discharge depth and 2 atmospheres, after 1000 cycles, the discharge capacity is measured as a percentage of the initial capacity.
[0059] Specifically, by comparing Examples 1-8 with Comparative Examples 1-3, the battery capacity attenuation of the metallized plastic current collector copper foil using ultrasonic assisted deposition is small. The improvement of corrosion resistance and adhesion caused by the grain refinement effect will further improve the electrode stability and ultimately further improve the cycle life of the lithium battery.
[0060] In summary, the current collector of ultrasound-assisted directional energy deposition and its preparation method and system apply an ultrasonic field in an acidic sulfate system, so that the Cu deposition process is transformed from diffusion control to electrochemical control, which accelerates the mass transfer process and improves the Cu electrodeposition effect; at the same time, ultrasound has a grain refinement effect. In the process of using ultrasonic impact to assist deposition, the microcrystalline structure on the surface of the composite copper foil can be increased, thereby increasing the contact angle between the composite current collector copper foil and the electrolyte, reducing the wettability between the two, thereby reducing the corrosion of the electrolyte to the composite current collector copper foil and improving the electrolyte resistance of the film layer; in addition, the refined grains make the surface of the composite current collector copper foil rough, which helps to improve its adhesion to the active material, thereby improving the conductivity and structural stability of the electrode. The above effects can ultimately further improve the cycle life of the lithium battery.
[0061] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a current collector for ultrasound-assisted directed energy deposition, characterized in that: The steps include: Step S1, sputtering Cu on the surface of the substrate layer by magnetron sputtering to obtain a carrier foil; Step S2, electrodepositing copper on the carrier foil in an acidic sulfate system to obtain a Cu layer, and simultaneously subjecting the carrier foil to ultrasonic impact treatment, wherein the frequency of the ultrasonic wave is 10-30 MHz and the power does not exceed 100 W.
2. The method for preparing a current collector for ultrasound-assisted directed energy deposition according to claim 1, characterized in that: The step S1 of sputtering Cu on the surface of the substrate layer by magnetron sputtering specifically includes the following steps: Step S11, adjusting the vacuum degree of the chamber of the magnetron sputtering plating machine, and starting the cathode and the transmission roller; Step S12, introducing argon gas into the chamber and increasing the power of the ion source to ionize the argon gas, thereby cleaning the surface of the substrate; Step S13, introducing sputtering gas argon gas, and using a copper target to form a Cu layer on the surface of the substrate layer by magnetron sputtering, so as to obtain a carrier foil; Step S14, repeating steps S11-S13 on the other side of the substrate layer.
3. The method for preparing a current collector for ultrasound-assisted directed energy deposition according to claim 2, characterized in that: The power adjustment range of the ion source in step S12 is 800-1000W.
4. The method for preparing a current collector for ultrasound-assisted directed energy deposition according to claim 2, characterized in that: In the step S13, the purity of the sputtering gas argon is not less than 99.99%, the amount of the sputtering gas is 400-600 sccm, the pressure in the chamber is in the range of 0.3-0.5 Pa, and the power of the magnetron sputtering is 5-50 Kw.
5. The method for preparing a current collector for ultrasound-assisted directed energy deposition according to claim 1, characterized in that: The thickness of the Cu layer after thickening in step S2 is 500nm-5μm.
6. The method for preparing a current collector for ultrasound-assisted directed energy deposition according to claim 1, characterized in that: The power of the ultrasonic impact treatment in step S2 is 20-60W.
7. A current collector for ultrasound-assisted directed energy deposition prepared by the method according to any one of claims 1 to 6, characterized in that: include: substrate layer; A Cu layer is provided on both sides of the substrate layer.
8. The current collector for ultrasound-assisted directed energy deposition according to claim 7, characterized in that: The substrate layer comprises any one of a biaxially oriented polypropylene film, a cast polypropylene film, a polyethylene terephthalate film, a polyimide film and a polyethylene naphthalate film; The thickness of the substrate layer is 3-20 μm.
9. The current collector for ultrasound-assisted directed energy deposition according to claim 7, characterized in that: The material of the Cu layer is copper or copper alloy; The thickness of the Cu layer is 500nm-5μm.
10. An ultrasound-assisted directed energy deposition system, characterized in that: The current collector is prepared by the method according to any one of claims 1 to 6, characterized in that it comprises: An electroplating bath, wherein an acidic sulfate system is provided in the electroplating bath; and At least one ultrasonic generator is arranged above the electroplating pool.
Citation Information
Cited By
Method for quantitatively controlling grain size of electro-deposition copper foil through power ultrasound
CN120866892A
Ultrasonic vibration treatment method for composite current collector and composite current collector
CN122446182A
